(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
Valuable employees belong to the most important category of personnel, since they are the main pushing force of the organization, and their absence will be very noticeable for the company. To prevent the loss of such personnel in a timely manner, the most optimal interaction is necessary, taking into account the interest of all parties. The article discusses the basic principles of retaining valuable employees.